2021
DOI: 10.3934/microbiol.2021029
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities encountered by sulfur nanoparticles combating Staphylococcal species harboring scc<i>mec</i>A recovered from acne vulgaris

Abstract: <abstract> <p>Over decades, sulfur has been employed for treatment of many dermatological diseases, several skin and soft tissue, and <italic>Staphylococcus</italic> infections. Because of its abuse, resistant bacterial strains have emerged. Nanotechnology has presented a new horizon to overcome abundant problems including drug resistance. Nano-sized sulfur has proven to retain bactericidal activity. Consequently, the specific aims of this study are exclusively directed to produce vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…In the late finishing period, the IgG concentration linearly increased because inorganic sulfur supplied in the feed was activated to combine with organic compounds in the animal body and then could provide a bioavailable sulfur source [ 25 ], and more sulfur-containing amino acids then accumulated in the body, which could indirectly enhance the immunity of growing-finishing pigs and improve the anti-inflammatory symptoms [ 26 ]. However, some reports have shown that NTS has antibacterial functions in vivo and in vitro [ 4 , 27 ], but it is not certain that dietary NTS could directly affect the production and secretion of immunoglobulin in swine. Therefore, the addition of NTS as a new additive to animal feed requires more research to explore the relationship between the immune system and the action of NTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late finishing period, the IgG concentration linearly increased because inorganic sulfur supplied in the feed was activated to combine with organic compounds in the animal body and then could provide a bioavailable sulfur source [ 25 ], and more sulfur-containing amino acids then accumulated in the body, which could indirectly enhance the immunity of growing-finishing pigs and improve the anti-inflammatory symptoms [ 26 ]. However, some reports have shown that NTS has antibacterial functions in vivo and in vitro [ 4 , 27 ], but it is not certain that dietary NTS could directly affect the production and secretion of immunoglobulin in swine. Therefore, the addition of NTS as a new additive to animal feed requires more research to explore the relationship between the immune system and the action of NTS.…”
Section: Resultsmentioning
confidence: 99%
“…However, some reports have shown that nontoxic sulfur has antibacterial functions in vivo and in vitro [4,27], but it is not certain that dietary nontoxic sulfur could directly affect the production and secretion of immunoglobulin in swine. Therefore, the addition of nontoxic sulfur as a new additive to animal feed requires more research to explore the relationship between the immune system and the action of nontoxic sulfur.…”
Section: Immune Responsementioning
confidence: 99%
“…28 Recently, sulfur nanoparticle preparations have demonstrated effectiveness against Staphylococcus bacteria. 29 Staphylococcus bacteria can affect acne pathogenesis by introducing drug resistance virulence factors. 30…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…Sulfur interacts with cysteine in keratinocyte to produce hydrogen sulfide that can rupture disulfide bonds, causing a keratolytic effect 28 . Recently, sulfur nanoparticle preparations have demonstrated effectiveness against Staphylococcus bacteria 29 . Staphylococcus bacteria can affect acne pathogenesis by introducing drug resistance virulence factors 30…”
Section: Acne Treatmentsmentioning
confidence: 99%
“…In this context, environmental biofilms and their associated virome serve as reservoirs for antimicrobial resistance [10] . The development of nanoparticles with antibacterial activity is one of the solutions for combating bacteria that are multi-resistant to antibiotics [11] .…”
mentioning
confidence: 99%